Overcoming reading comprehension difficulties through a prosodic reading intervention: A single-case study. (February 2019) - Calet, Nuria; Pérez-Morenilla, M. Carmen; De los Santos-Roig, Macarena
Apart from speed and accuracy, prosody has recently been included as another component of skilled reading, as its role in reading comprehension is being increasingly recognized. Prosodic reading refers to the use of prosodic features of language during reading, including suitable pauses, stress and intonation and appropriate phrasing. The aim of this research was to examine the impact of a prosodic reading intervention on the reading comprehension of a fourth-grade primary child with specific reading comprehension difficulties. An AB single-case design was used with baseline (A) and treatment (B) phases. The intervention, in 17 sessions, was based on repeated reading with a focus on expressiveness. Results pointed to improved reading fluency and reading comprehension scores over baseline scores. Nevertheless, more studies are needed to show conclusive evidence for improved comprehension as a result of prosody intervention. The implications of prosodic reading interventions for literacy development are discussed.